Vascular inflammation and cardiovascular burden in metastatic breast cancer female patients receiving hormonal treatment and CDK 4/6 inhibitors or everolimus. (25th November 2020) - Papageorgiou, C; Zagouri, F; Dimopoulos, M; Manios, E; Kafouris, P; Tousoulis, D; Anagnostopoulos, C; Toutouzas, K
Abstract: Background: Chemotherapy regimens for breast cancer treatment can promote vascular dysfunction and lead to high cardiovascular risk. Purpose: The aim of this study was to investigate the cardiovascular burden and vascular inflammation in metastatic breast cancer patients receiving either CDK 4/6 inhibitors and hormonal treatment or standard everolimus and hormonal treatment. Methods: 22 consecutive female patients with metastatic breast cancer that expressed estrogen and /or progesteron receptor and were HER2-negative were enrolled. Patients with active infection, chronic autoimmune disease and history of chemotherapy for the metastatic disease and/or adjuvant chemotherapy during the past 3 years were excluded. All subjects received hormonal treatment and of those, 10 received everolimus and 12 received therapy with CDK 4/6 inhibitors. The two groups were matched for age, history of hypertension, diabetes, dyslipidemia, smoking and all were free of major cardiovascular events for the past 6 months. Regional wall thickness (RWT) and left ventricle mass (LVM) measurements by transthoracic echocardiographic study were obtained followed by 24 hour ambulatory blood pressure monitoring, and 18F-fluorodeoxyglucose positron-emission tomography/computed tomography imaging. Radiotracer uptake in the aortic wall (ascending, arch, descending, abdominal), was quantified as tissue-to-background ratio (TBR).Each patient was assessed for the aforementioned parameters before the initiation and after 6 months of treatment. Results: At follow up, patients assigned to CDK4/6 treatment demonstrated increased measurements of 24 hour systolic blood pressure (SBP) (p=0.004), daytime SBP(p=0.004) and night time SBP (p=0.012) (Group effect). The 24 hour mean arterial pressure measurements were also higher in CDK 4/6 population, in comparison to everolimus that displayed firm values. (Group effect- p=0.035, Interaction effect-p=0.023).Additionally, 24 hour diastolic blood pressure recordings in CDK 4/6 therapy were higher opposed to everolimus that remained consistent (Interaction effect- p=0.010). In CDK 4/6 group, TBR aorta measurements also increased significantly, whereas TBR values in everolimus remained stable. (Interaction effect-p=0.049). Both therapeutic regimens displayed statistically significant damaging effect with regards to the following variables: Night-time SBP (p=0.032), RWT (p<0.001), and LVM (p<0.001). Conclusion: Chemotherapy with novel CDK 4/6 inhibitors and hormonal treatment can lead to increased vascular inflammation, and higher blood pressure values compared to the combination of everolimus and hormonal treatment in female patients with HR-positive HER2-negative metastatic breast cancer. Moreover, both treatment strategies promote remodelling of the left ventricle by means of increased RWT and mass. Further research and longitudinal studies in this field are required to validate the above findings. Funding Acknowledgement: Type of funding source: None